Hai mươi tám 28 Black styles for student practice - Young, Young (Milady Pub. Co., 1992)
Designed to give students and professionals practice in the specialized area of black styling, this comprehensive resource covers the diverse area of cutting, setting, comb-out and blow-drying. Full, two-page layouts of each style allow stylists to easily learn procedures and techniques. Text is based on the concept of developing and refining stylists' skills through practice on a mannequin